HYGIENIC ANALYSIS OF THE CONSUMPTION OF CARBOHYDRATES AND PRESERVATIVE PRODUCTS IN PATIENTS WITH PERIODONTISSIS - Dilshod Shavkatovich Alimukhamedov; Bakhtiyor Baimanovich Kholbekov (Innovate Conferences, 2025)
In today's era of development, one of the urgent problems of modern nutrition is to prevent diseases by promoting healthy eating among various segments of the population, as well as to create conditions for preventing the complications of various nutritionally related diseases that arise due to a lack of animal proteins and fats, vitamins and minerals in the daily diet [1,2,3,5,7].